The Relationship Between Stress Levels And The Severity of Acne Vulgaris In Medical Students At Prima Indonesia University Class of 2022 - Tarisa Mudhia Putri; Ade Arhamni; Lisdawaty Siregar (International Journal of Health and Pharmaceutical (IJHP), 2025)
Acne vulgaris is a chronic skin disease of the pilosebaceous follicle with multifactorial etiology. Psychological stress represents one significant etiological factor, as stress activates the hypothalamic-pituitary-adrenal axis, stimulating corticotropin-releasing hormone, which plays an important role in acne vulgaris development. Medical students experience high academic burdens that potentially cause stress, making them more susceptible to acne vulgaris with varying severity degrees. This cross-sectional analytic observational study investigated the relationship between stress levels and acne vulgaris severity among medical students at Universitas Prima Indonesia, class of 2022. A total of 35 respondents were selected through stratified random sampling. Data were collected using the Depression Anxiety Stress Scale-42 to measure stress levels and the Lehmann Acne Grading System to assess acne severity. Results showed that 60.0% of respondents experienced moderate stress, while 45.7% exhibited mild acne vulgaris. Chi-Square testing revealed a statistically significant relationship between stress levels and acne severity (p = 0.000). A clear dose-response pattern emerged, with mild stress predominantly associated with mild acne, moderate stress with moderate acne, and severe stress universally manifesting as moderate-to-severe acne manifestations. This investigation concludes that a significant correlation exists between stress levels and acne vulgaris severity in this population, necessitating stress management interventions and mental health education programs to reduce acne severity risk among medical students.